Ancient Boats in North-West Europe : the Archaeology of Water Transport to AD 1500. - McGrail, Sean (Longman archaeology series., 2014)
At last a paperback edition of this standard work on marine archaeology. Séan McGrail's study received exceptional critical acclaim when it was first published in hardback in 1987 and it is now revised and published in paperback for the first time. Professor McGrail provides an authoritative survey of water transport across Northern Europe from the Late Palaeolithic to the later Middle Ages, using evidence of excavations, but also documentary sources, iconographic and ethnographic evidence. In the process he answers such key questions as How were these boats built? What sort of environment wer.